Inteligência Artificial e teoria ator-rede em diálogo: analisando atores e associações - Catalano, José Victor Rodrigues (2023)
The main focus of this research is to deepen the critical understanding of Artificial Intelligence (AI) in the context of Studies in Science, Technology and Society (STS) through a scientific approach. We seek to apply Actor-Network Theory (ANT) to analyze the complex interaction of AI with scientific, technological and social dimensions. The underlying purpose is to consider AI as a social construction, through the analysis of its evolutionary dynamics and the identification of the main actors involved in this scenario, as well as their respective associations. In a complementary way, we present a chronological synthesis that addresses the most significant events that shaped the history of AI, including the investigation of the origins and motivations that contributed to its development over time. This provides an understanding of the historical influences that develop into the shape of modern AI. Finally, we focus our efforts on examining the intricate interplay of AI with dimensions of the STS field, which involves an investigation of ethical, political, economic, and cultural impacts of AI on society. We recognize that the influence of AI transcends the technical and scientific scope, extending to crucial areas of society. From an ANT perspective, we highlight the importance of understanding AI not as a neutral technology, but rather as an active participant in a complex and interconnected socio-technical scenario, influencing and being directly influenced by a wide range of actors, whether human or not humans.